Financial development, foreign direct investment and economic growth: panel causality approach - Veselinović, Nevena; Despotović, Danijela (Industrija, 2022)
The examination considers the causality between banking sector depth, foreign direct investment, and economic growth in the sample of six Central and Eastern European countries in the period range between 2000 to 20118. Utilizing the Dumitrescu and Hurlin (2012) panel causality test, the results confirmed a supply-leading hypothesis, FDI-led growth hypothesis, and unidirectional causality from the banking sector depth to foreign direct investment. As the causality ranging from the depth of the banking sector to foreign direct investment and economic growth has been confirmed, the conclusion is that attention should be focused on policies that promote the development of the banking sector. In this way, a well-regulated banking sector will attract more FDI, which will lead to higher growth rates in the analyzed countries.